Evaluating the association between the SHANK3 gene and bipolar disorder. (30th October 2016) - Zhang, Chen; Wu, Zhiguo; Hong, Wu; Peng, Daihui; Fang, Yiru
Abstract: Background: Previous studies have shown that the genes involved in synaptic density and plasticity were downregulated in bipolar disorder (BD) postmortem brains. The SHANK 3 (SH3 and multiple ankyrin repeat domain 3) protein is a scaffold protein enriched in the postsynaptic density of excitatory synapses, and recent findings were suggestive of a possible role of SHANK 3 in the development of BD. In this study, we aimed to evaluate the genetic association between the gene encoding SHANK 3 (SHANK 3 ) and BD in Han Chinese. Methods: Ten variants in SHANK 3 were genotyped among 1482 individuals with or without BD. We measured the mRNA expression level of SHANK 3 in patients with BD and controls. We then performed an eQTL analysis. Results: In our sample set, there were no significant differences in allele, genotype and haplotype frequencies between the BD and control groups. Our results showed no significant difference in the level of peripheral SHANK3 expression between the BD patients and healthy controls. Further eQTL analysis showed that rs9616915 has functional effect on SHANK3 expression in the hippocampus. Conclusion: This study does not provide evidence for a major role of SHANK3 in the pathogenesis of BD. Highlights: The first association study of SHANK3 gene with bipolar disorder (BD). Peripheral SHANK 3 mRNA expression was examined in drug-naïve BD patients and healthy controls. While no significant association was observed in Han Chinese, rs9616915 might be marginally associated with BD in Europeans. SNP rs9616915 has a functional effect on the SHANK3 mRNA expression in the hippocampus.